Effects of a WeChat Mini-Program on Human Milk Feeding Rates in a Neonatal Intensive Care Unit During the COVID-19 Pandemic - Jiang, Chengyao; Chu, Xue; Yu, Zhangbin; Chen, Xiaohui; Zhang, Jun; Han, Shuping (Frontiers in Pediatrics, 2022)
Objective We investigated changes in maternal daily milk pumping frequency and milk volume per expression and their derived lactation indicators, as well as human milk (HM) feeding status with a focus on amount and rates in preterm infants admitted to the neonatal intensive care unit (NICU) after using a WeChat mini-program during the 2019 coronavirus (COVID-19) pandemic. Methods The study was conducted with 482 mothers and their 544 babies. We prospectively enrolled mothers and infants with birth weight <1,500 g or gestational age <32 weeks born in 2020, and retrospectively included the same population in 2019. All study subjects were classified into three subgroups: pre-pandemic (PP, 2019), early pandemic (EP, January to April 2020), and late pandemic (LP, May to December 2020). From 1 January 2020, mothers recorded in an online pumping diary using the WeChat mini-program. We obtained the infants’ feeding information from an online database for analysis. Results Maternal lactation indicators did not change significantly. However, 56.7% (139/245) of mothers achieved milk volume ≥500 ml/day (CTV) in PP, 58.9% (33/156) in EP, and a slight increase to 60.7% (91/150) in LP. Maternal pumping frequency remained about eight times/day. In LP, daily milk volume was higher than the other two periods from day 4, and mothers achieved CTV by day 12, which was achieved in the other two groups by 13–14 days. There were several statistical differences in the amount and rates of feeding between the groups, particularly about HM and donor milk feeding, with the vast majority being decreased during EP, while during LP they returned to PP levels. Pleasingly, the median average daily dose of HM at 1–28 days was highest in LP (LP, 87.8 vs. PP, 75.5 or EP, 52.6 ml/kg/day, Pcorrected < 0.001). In addition, most categorical feeding indicators decreased in EP and recovered in LP. Conclusion An education model based on the WeChat program could aid lactation education and management in mothers of preterm infants to maintain healthy lactation. The model, together with optimized management strategies, can ensure that the HM feeding rate is not compromised in vulnerable high-risk infants during NICU hospitalization in a public health emergency, like the COVID-19 pandemic.